PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA KELAS V SDS YKPP SUNGAI PAKNING KABUPATEN BENGKALIS - Rahman, Junaidah; Kurniaman, Otang; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This research carried out base of lower result of Indonesian language subject in grade 5th SDS YKPP Sungai Pakning Bengkalis Regency, which is about 69,84 within minimal completeness criterion stated is 75. Among 31 students, there were only 9 students that able to achieve the score of minimal completeness criterion stated. The purpose of this research is to increased student’s writing poem skill of the five grade at SDS YKPP Sungai Pakning Bengkalis Regency with the using of picture media. This research was classroom action research consisting 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After implementation of using of picture media and learning model it was obtained student’s outcomes in UH I within average 74.03(improved from basic score 5.9%). The average score form UH II was 84.36 (improved 20.7%). Teachers activities results in the first meeting of the first cycle was 50% (fair category), and then 62.5% (good category) for the second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 77.5% ( good category) and then 97.5% (very good category) for second meeting in cycle II. Students activity in the first meeting of the cycle I was 52.5% (enough category), 62.5% (good category) for the second meeting in the cycle I. And then in the first meeting of the second cycle was 75% (good category), 95% (very good category) for the second meeting in cycle II. Based on the result it can be concluded that implementation of using picture media in five graders at SDS YKPP Sungai Pakning Bengkalis Regency.Keywords :Using Picture Media , Increasing Writing Poem Skill.